פנחס ארצי הנלוסזת בתעודות אל־עמארנה. לחקר מסורת הכתיבה של הסיפרים בכנען ערב כיבוש הארץ - Artzi, Pinḥas
The “Glosses” in the el-Amarna Tablets. A Contribution to the Study of Cultural and Writing Traditions among the Scribes of Canaan before the Israelite Conquest.